Dobre smoki Krzysztofa Kamila Baczyńskiego - Klukas, Monika (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2001)
K. K. Baczyński is usually perceived as a poet of the Columbus Generation (especially in case of teenagers and Polish language students). His poetry is not really known to the Polish reader. Its knowledge is usually restricted to some standard poems, for example With the head on the gun (Z głową na karabinie) or The Generation (Pokolenie).Having kept track of Baczyński’s creative activity ever since the juvenile period up till the poems written a few months ahead of his death, it can easily be observed that his poetry is very fabulous, full of such characters as the king’s daughter, the mermaid, the aquarius, the knight and the glass mountain. The Dragon appears in 11 poems. It can be observed in the pre-war poems (e.g. Come, my good dragon - Przyjdi mój dobry smoku) as well as in the ones written during the occupation, for example The crystal Idyll (Idylla kryształowa). The dragon’s figure is perceived as the main character of the poem, the simile or the metaphor.All kinds of Baczyński’s “dragons’ presence” has been discussed or signalled in the article. The author seems to be intrigued by the two questions she is trying to give answers to: what is the function of dragons in Baczyński’s poems, any why is it a different dragon every time? A good example seems to be the poem Fault (Wina) where the author presents his own version оf the legend of St. George. The dragon is not a beast to be killed in order to save the imprisoned “blue-haired girl” . She felt safe. The dragon could be her protector or a friend. She is mourning for its death. It is the knight to be blamed not the dragon.All Baczyński’s dragons are good.